Β-Cyclodextrin functionalized carbon quantum dots as sensors for determination of water-soluble C60 fullerenes in water. Issue 9 (12th February 2016) - Cayuela, Angelina; Laura Soriano, M.; Valcárcel, Miguel
Abstract : A selective photoluminescence method based on Carbon Quantum Dots (CQDs) functionalized with carboxymethyl-β-cyclodextrin for the direct determination of water-soluble C60 fullerene has been developed. Abstract : A selective photoluminescence method based on Carbon Quantum Dots (CQDs) functionalized with carboxymethyl-β-cyclodextrin for the direct determination of water-soluble C60 fullerene has been developed. CQDs were synthesized using a top-down methodology from multiwall carbon nanotubes (MWCNTs) and further functionalized with N -Boc-ethylenediamine to confer monoprotected amine groups onto their surface. Once amine-functionalized CQDs were obtained after deprotection, an amidation reaction with carboxymethyl-β-cyclodextrin cavitands was achieved and the obtained fluorescent β-cyclodextrin functionalized Carbon Quantum Dots (cd-CQDs) were investigated for the inclusion complexation of water-soluble C60 . Quenching of their fluorescence was observed owing to the non-covalent self-assembly of cd-CQDs and C60, making possible the quantification of C60 . A method to determine water-soluble C60 is then proposed with detection and quantification limits of 0.525 and 1.751 μg mL −1, respectively. The method was validated by determining soluble C60 fullerene in spiked river water. One added value of the paper is the fact that it can be ascribed to the "Third Way in Analytical Nanoscience and Nanotechnology".